EFFECT OF DIFFERENCES BROMELAIN ENZYME CONSENTRATION ON PROTEIN HYDROLYSATE FROM WASTE OF TILAPIA VISCERA (Oreochromis sp.) ON ANTIOXIDANT ACTIVITY - Muhammad Athoillah Sholahuddin; Lastuti, Nunuk Dyah Retno; Amin, Muhamad (Jurnal Biosains Pascasarjana, 2024)
Tilapia is a commodity that is widely consumed by the public, especially in Indonesia. Fresh tilapia offal has a protein content composition of 55.55%, so to increase its selling value it is often made into protein hydrolysate. Protein hydrolysis using enzymes is an effective way, because it can make protein hydrolysates avoid damage to certain amino acids. Proteolytic enzymes have many types and one that can be used as a hydrolyzer, in producing protein hydrolysates is bromelain enzyme. The purpose of this study was to determine the effect of proteolytic enzyme type and hydrolysis time on antioxidant activity of protein hydrolysate from Oreochromis sp. offal waste. This study used RAL 2 factors and each was repeated 3 times. The first factor was the concentration of bromelain enzyme used, namely control concentration, 1%, 2% and 3%. The second factor was the hydrolysis time, which was 4 hours, 6 hours and 8 hours. The data obtained were analyzed and continued with antioxidant activity test, hydrolysis degree test and protein content test. The best concentration of bromelain enzyme as antioxidant was 3% concentration for 6 hours hydrolysis with IC50 value of 82.53µg/mL, the best DH of 82.25%±4.03 and the highest protein content of 54.55%. Keywords: Antioxidant, bromelain enzyme, tilapia offal, protein hydrolysate